Faktor – Faktor yang Mempengaruhi Return Saham pada Perusahaan Property di Bursa Efek Indonesia - St. Arafah. H; Arsal, Muryani; Badollahi, Ismail (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aims to analyze factors influencing stock returns of property sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Independent variables examined include Debt to Equity Ratio, Growth, Firm Size, Net Profit Margin, and Earning Per Share, with stock return as the dependent variable. The research population comprises 60 property companies, with a sample of 8 companies meeting purposive sampling criteria. Secondary data is obtained from financial reports published on the Indonesia Stock Exchange official website. The analysis method uses multiple linear regression with panel data, accompanied by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. Hypothesis testing is conducted partially (t-test) and simultaneously (F-test), along with coefficient of determination (R2) analysis. The research results are expected to provide insights into the influence of financial factors on stock returns of property companies, thus serving as a consideration for investors in making investment decisions in this sector.